JAK/STAT in human diseases: a common axis in immunodeficiencies and hematological disorders - Djidjik, Reda; Lamara Mahammed, Lydia; Berkani, Lilya Meriem; Allam, Ines; Benmoussa, Alaa Hamidou; Gharnaout, Merzak; Belaid, Brahim (Frontiers in Immunology, 2025)
The JAK-STAT signaling pathway (Janus Kinase-Signal Transducer and Activator of Transcription) is a crucial molecular cascade that regulates immune responses, cell proliferation, and hematopoiesis. Germline or somatic mutations affecting this pathway leads to a wide range of pathologies, from severe immunodeficiencies to inflammatory and autoimmune diseases, as well as hematologic malignancies. Loss-of-function mutations impair cytokine signaling and primarily result in immunodeficiency, while gain-of-function mutations cause excessive pathway activation, promoting autoimmune diseases and myeloproliferative syndromes. Advances in our understanding of the JAK-STAT pathway and its involvement in various diseases have opened new perspectives in precision medicine and targeted therapies including JAK inhibitors (JAKi), gene therapy, and hematopoietic stem cell transplantation (HSCT). A detailed understanding of specific mutations and their effects on intracellular signaling allows for the refinement of therapeutic strategies and optimization of patient management. In this review, we examined the biology of the JAK-STAT pathway, highlighted the key pathogenic mutations and their clinical consequences, and described the laboratory and diagnostic approaches used to investigate this pathway.